Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1051/e3sconf/20171700036
|View full text |Cite
|
Sign up to set email alerts
|

A concept development of an early warning system for toxic sewage detection

Abstract: Abstract. The article presents a concept of an EWS (early warning system) for toxic sewage detection upstream from Wroclaw Wastewater Treatment Plant. It includes design and construction of three toxicity warning stations, situated in municipal sewage system. Early detection of toxic contaminants provides time for corrective actions. Wastewater toxicity level is based on activated sludge OUR (Oxygen Uptake Rate) measurement. The database of normal level of activated sludge OUR is collected during the measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Large percentage (> 94%) of the cefotaxime-resistant E. coli exhibited multiple antibiotic indices (MAR Index) > 0.2 which means that the isolates might have originated from high risk source (s), where antibiotics are probably abused [38,40,59]. As noted earlier, since the WWTPs are known as early warning systems [47], the MAR Indices in this study revealed that antibiotics are in constant abuse and hence, their high selective pressure [61]. The high resistance to colistin sulphate (76.5%) detected in this study is considered alarming.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Large percentage (> 94%) of the cefotaxime-resistant E. coli exhibited multiple antibiotic indices (MAR Index) > 0.2 which means that the isolates might have originated from high risk source (s), where antibiotics are probably abused [38,40,59]. As noted earlier, since the WWTPs are known as early warning systems [47], the MAR Indices in this study revealed that antibiotics are in constant abuse and hence, their high selective pressure [61]. The high resistance to colistin sulphate (76.5%) detected in this study is considered alarming.…”
Section: Discussionmentioning
confidence: 94%
“…The presence of the latter (cefotaxime-resistant E. coli) might also be due to wastewater from hospital inflow. These resistance attributes are expected from the clinical origin [20,21,46] and since the WWTPs are known as early warning system [47], the presence of a large number of cefotaximeresistant E. coli might be a warning sign of probable lack of pretreatment for the hospital outflow. The effluent concentration of both total E. coli and cefotaxime-resistant E. coli (range in log 10 CFU/mL = 0 to 0.3) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In extreme cases the bacteria are killed by toxic wastewater, and there is a need for cleanout and reseeding of plant, which is a costly and time-consuming operation [2]. Toxic inflow can cause collapse of nitrification process and lead to significantly exceeded total nitrogen concentration in effluent [4]. Wastewater streams from drug manufacturing also contain residues of active pharmaceutical ingredients (API) and their intermediates, which are classified as micropollutant of emerging concern.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes, antibodies, microorganisms or DNA could be used as biological sensing element of biosensor in combination with an appropriate transducer (e.g., electrochemical, optical, colorimetric or piezoelectric) [19]. Wastewater treatment plant can be equipped with early warning system that includes a few toxicity measurement points placed at selected locations [4].…”
Section: Introductionmentioning
confidence: 99%